Dragons at Crumbling Castle : and other stories - Pratchett, Terry; Beech, Mark, 1971- (Boston : Clarion Books, Houghton Mifflin Harcourt, 2015)
An illustrated collection of fourteen short stories featuring "dragons and wizards, councilors and mayors, an adventurous tortoise and a monster in a lake, along with plenty of pointy hats and a few magic "spells" written when the author was a teenaged newspaper reporter.
Dragons at Crumbling Castle -- Hercules the tortoise -- Great Speck -- Hunt the Snorry -- Tales of the Carpet People -- Dok the Caveman -- Big Race -- Another tale of the Carpet People -- Great Egg-dancing Championship -- Edwo, the boring knight -- 59A bus goes back in time -- Abominable Snowman -- Blackbury monster -- Father Christmas goes to work.
Booklist
Publisher's Weekly
School Library Journal
Booklist, December 2014
Kirkus Review, December 2014
Publisher's Weekly, December 2014
Keywords: Humorous stories; Short stories; Humorous fiction; Short stories; Humorous fiction; Short stories